2021
DOI: 10.21203/rs.3.rs-486904/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Yoga Nidra vs Supine Relaxation Technique on Depression, Anxiety, Insomnia in frontline COVID-19 Health Care Workers: A Randomized Controlled Trial

Abstract: Background Mental health disturbances have been well documented due to COVID-19 pandemic. There was surge in literature about use of various Mind Body Therapies during pandemic to curb these disturbances. But none have been studied to prospectively during COVID-19 pandemic. Hence, present study was planned to evaluate the efficacy of Yoganidra in frontline Health care workers (HCW) during pandemic using online and digital tools. Methods This open label randomized trial consisting of 2 arms (Yoganidra and Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Another study by Rani et al has explained that psychological problems like anxiety and depression can be improved significantly with Yoga Nidra [ 29 ]. Gunjiganvi et al have determined that Yoga Nidra showed the benefits of improvement in depression and anxiety [ 30 ]. Slow Pranayama techniques generate inhibitory signals and hyperpolarizing current within neural and nonneural tissue by mechanically stretching the tissues during breath inhalation and retention.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Rani et al has explained that psychological problems like anxiety and depression can be improved significantly with Yoga Nidra [ 29 ]. Gunjiganvi et al have determined that Yoga Nidra showed the benefits of improvement in depression and anxiety [ 30 ]. Slow Pranayama techniques generate inhibitory signals and hyperpolarizing current within neural and nonneural tissue by mechanically stretching the tissues during breath inhalation and retention.…”
Section: Discussionmentioning
confidence: 99%
“…Research on yoga-nidra is still in its evolutionary phase, however, studies to date suggest its efficacy in coping with depression, anxiety and insomnia (11)(12)(13)(14). It's been shown to increase alpha brain wave activity (15), Heart Rate Variability (HRV) (16), and Dopamine secretions (17), all three of which are considered strong measures of the body's stress accommodation response.…”
Section: Discussionmentioning
confidence: 99%
“…Furhtermore, the researchers discussed the treatment mechanisms of music therapy through reduction the activity of the hypothalamic pituitary and adrenal axis, leading to dowmregulation of cortisol level, eventually improved functions of psycho-neuro-immune-endocrine. Therefore, the researchers suggested that music can also be used to effectively improve the subjects' negative emotions such as fatigue, sadness, fear, and worry, which is suitable for staffs who worked with high-stress conditions [10].…”
Section: Music Treatment Of Insomnia In Duration Of Covid-19 Pandemicmentioning
confidence: 99%